Subcommittee on Depreciation Accounting- Proposed Statement International Accounting Standard (IASC) of the Committee on Financial Accounting Standards. (The Accounting Review, 1977)
This article presents the text of a report by the Subcommittee on Depreciation Accounting regarding the proposed accounting standard by the International Accounting Standards Committee of the American Accounting Association in the U.S. as of October 2, 1977. The proposed standard ought to provide a conceptual foundation for depreciation accounting. The point should be made rather forcefully that for income determination purposes the depreciation charge for a period ideally measures the cost or other basic value of the asset services consumed in that period. The statement, in paragraphs 10 and 21, and perhaps elsewhere, should tie the process of depreciation to the consumption of the service potential of the asset, at least conceptually and for income determination purposes. The statement could recognize the difficulties involved in specifying what is meant by services or service potential and the problems involved in measuring their consumption. A general guideline should be presented that in choosing a depreciation method, due care must be paid to the anticipated pattern of service consumption.